The influence of adding red galangal simplicia (Alpinia purpurata K Schum.) on the chemical, organoleptic, and antioxidant activity of soursop leaf tea (Annona muricata L.) - Maulidya, Farah Nabila; Hidayah, Nurul (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Herbal tea imparts health benefits largely due to its polyphenol-based antioxidant activity. Soursop leaves contain compounds including flavonoids, tannins, alkaloids, acetogenins, and saponins. Red galangal contains compounds such as saponins, tannins, flavonoids, and essential oils. The addition of red galangal to soursop leaf tea not only enhances the antioxidant activity of the tea but also improves its flavor. This study investigated the influence of adding red galangal simplicia to soursop leaf tea on its chemical and organoleptic properties, and also its antioxidant activity. The research method was based on varying ratios of the two ingredients (soursop leaves: red galangal simplicia), specifically F1 (100%: 0%), F2 (85%: 15%), F3 (80%: 20%), F4 (75%: 25%), F5 (70%: 30%), with three repetitions. The chemical properties tested included water content, ash content, antioxidant activity, flavonoid content, polyphenol content, and tannin content. The organoleptic tests included assessments of color, aroma, taste, aftertaste, and overall preference. The results demonstrated that soursop leaf tea with the addition of red galangal simplicia had a significant effect on its chemical properties, organoleptic properties, and antioxidant activity. The analysis results showed the lowest water content at 8.51% (F5), the lowest ash content at 7.03% (F5), the highest antioxidant activity at 33.37 ppm (F5), the highest flavonoid content at 95.46 mgQE/g (F5), the highest total phenolic content at 46.10 mgGAE/g (F5), and the highest tannin content at 42.63 mgCE/g (F5). Organoleptic assessment based on color preference scored 3.83 (F1), with the highest aroma score at 3.70 (F5), the highest taste score at 3.51 (F5), the highest aftertaste score at 3.30 (F5), and the highest overall preference score at 3.58 (F5). Based on these results, it can be concluded that the most preferred treatment, with the highest phytochemical contents and antioxidant activity, was treatment F5 with a concentration of 70% soursop leaves and 30% red galangal simplicia.